Pengaruh Kepemilikan Institusional, Ukuran Perusahaan, Dan Manajemen Aset Terhadap Nilai Perusahaan - Anthony Holly; Robert Jao; Ana Mardiana; Paulus Tangke (JAF (Journal of Accounting and Finance), 2023)
The purpose of study is to investigate the impact of institutional ownership, firm size, and asset management to firm value. Sample of this research is companies listed in Indonesia Stock Exchange between 2016-2018. Sample selected by purposive sampling method resulting 44 company as sample. Data type used in this study is quantitative data and analyzed using multiple regression analysis to analysis dependent variable, firm value and independent variable, institutional ownership, firm size, and asset management. The result of the research revealed institutional ownership and firm size have positive and significant effect to firm value because the mechanism of control by institutions is more effective and the bigger of the companies means their manager can accumulate value. Asset management has no effect to firm value Keywords : Institutional Ownership, Size, Asset Management, Firm Value